Designing a Promotional Media Website for Pottery Products Using the Waterfall Method - Miftahul Madani; Haryono Haryono (Jurnal Bumigora Information Technology (BITe), 2023)
Background: Penujak Village is one of the oldest pottery tourism villages that has succeeded in providing pottery production for foreign collectors. After the Bali bombing incident, Penujak pottery experienced a decline, which could trigger several other factors, including the development of promotions. Promotions used by the Penujak community still use traditional word-of-mouth promotions.Objective: This research aims to create a website to help promote pottery products in Penujak Village. Methods: This research uses a qualitative approach with the waterfall system development method.Result: The research produced website promotion interval values of 29, 1 being > 26, 6 31, 2 which can be categorized as 4 = Agree.Conclusion: Pottery promotional media in the Penujak tourist village is suitable for use as promotional media. Tests were carried out on promotional media using usability theory with seven questions fulfilled.